Cost-effectiveness of HIV treatment as prevention in serodiscordant couples. - Walensky, Rochelle P; Ross, Eric L; Kumarasamy, Nagalingeswaran; Wood, Robin; Noubary, Farzad; Paltiel, A David; Nakamura, Yoriko M; Godbole, Sheela V; Panchia, Ravindre; Sanne, Ian; Weinstein, Milton C; Losina, Elena; et al. (The New England journal of medicine, 2013)
The cost-effectiveness of early antiretroviral therapy (ART) in persons infected with human immunodeficiency virus (HIV) in serodiscordant couples is not known. Using a computer simulation of the progression of HIV infection and data from the HIV Prevention Trials Network 052 study, we projected the cost-effectiveness of early ART for such persons.
Keywords: Adult; Anti-Retroviral Agents; Cost-Benefit Analysis; Disease Transmission, Infectious; Drug Administration Schedule; Female; Gross Domestic Product; Health Care Costs; HIV Infections; Humans; India; Male; South Africa